Risk Factors for Postoperative Complications among the Elderly after Plastic Surgery Procedures Performed under General Anesthesia. (8th July 2018) - Fukui, Kiyoko; Fujioka, Masaki; Yamasaki, Kazumi; Yamakawa, Sho; Matsuo, Haruka; Noguchi, Miho
Abstract : Background . The frequency of surgery involving elderly patients has been increasing. The use of free tissue transfers in the elderly has been examined previously (Howard et al., 2005, Hwang et al., 2016, Grammatica et al., 2015, Serletti et al., 2000, and Sierakowski et al., 2017), whereas there have not been any such studies of plastic surgery procedures. We evaluated the risk factors for complications after plastic surgery procedures performed under general anesthesia in patients aged ≥75 years. Methods . The cases of patients aged ≥75 years who underwent plastic surgery procedures under general anesthesia at the Department of Plastic and Reconstructive Surgery, National Hospital Organization Nagasaki Medical Center, between 2009 and 2016 were reviewed retrospectively. Multiple logistic regression analysis was used to identify the risk factors for postoperative complications. Results . Two hundred and sixty-three cases were reviewed. Complications were seen in 137 patients. Age was not predictive of complications. The risk factors included a serum albumin level of <2.8 g/dl (odds ratio (OR): 2.96), an operative time of ≥120 min (OR: 6.22), and an American Society of Anesthesiologists performance status of ≥3 (OR: 2.39). Conclusions . Age is not contraindication for surgery in the elderly. It is important to assess comorbidities and perform surgical procedures as soon as possible to shorten the surgical period.